Language Input, Learning Environment, and Motivation of Successful Indonesian EFL - Medlin Bulain; Endar Rachmawaty Linuwih (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2023)
Second language acquisition is the process of learning the second language after an individual's first language has been established. The successful second language learner is affected by many factors. Three significant Second Language Acquisition (SLA) factors are Language Input, Learning environment, and motivation. This descriptive qualitative research aims to analyze the three significant components of SLA of two successful EFL undergraduate students, as evidenced by their advanced TOIEC scores and academic transcript demonstrating great achievement in English. This research shows that the language inputs of the two participants come from both inside and outside the classroom. The learning environment experienced by the participants included all three types of SLA learning environments: physical, psychological, and academic. Moreover, both participants have instrumental motivation, followed by intrinsic and extrinsic motivations